Generation Z Employee Engagement Measurement Model Using Gallup Q12 in the Hospitality Industry: A Study at Villa Seminyak, Bali - I Wayan Eka Sudarmawan; Purnantara, I Made Hadi; Saputra, Kadek Wira Adi (Lembaga Pengembangan Kinerja Dosen, 2025)
Employee engagement is a strategic factor for the hospitality industry because service quality is greatly influenced by employee commitment and involvement. This study aims to develop an employee engagement measurement model specifically for Generation Z employees at Villa Seminyak using the Gallup Q12 instrument. The research method uses a quantitative descriptive approach through the distribution of questionnaires to 34 Gen Z employees. The results show that the Basic Needs (Q1–Q2) and Teamwork (Q7–Q10) dimensions obtained the highest scores, while the Growth dimension (Q11–Q12) was the weakest aspect. These findings confirm that Gen Z requires role clarity, social support, and a collaborative work environment, but has high demands on career development and coaching. This study produces a Gen Z Employee Engagement model based on the Gallup Q12 combined with the psychological context and generational characteristics. This model can be used as a basis for developing HR strategies to improve employee engagement and hotel service quality